A Novel Endosteal Reconstruction of the Femur from Distal Femoral Remnant Using 3D-Printed Titanium Rings: A Two-Case Report. Issue 3 (July 2021) - Huang, Yong; Zhou, Yixin; Shao, Hongyi; Yang, Dejin; Tang, Hao; Guo, Shengjie
Abstract : Case: Femur reconstruction with only the distal femoral remnant is challenging because of poor bone volume required for stem fixation. Although proximal femoral replacement, total femur replacement, allograft prosthesis composite, and custom porous tantalum implants are options, hybrid fixation enhanced by endosteal reconstruction with three-dimensional (3D)-printed porous titanium rings to reconstruct the femur without supporting isthmus has not been described. We report 2 cases with satisfactory 34- and 22-month follow-up results of hybrid fixation enhanced by endosteal reconstruction with 3D-printed porous titanium rings. Conclusion: This novel method provides a solution to revise loosened femoral endoprosthesis with only distal femoral remnant.